: Efektivitas Kombinasi Insektisida Nabati Daun Sirsak dan Daun Belimbing Wuluh Sebagai Pengendali Hama Crocidolomia pavonana F - Dinda Fahrun Nisa (Fakultas Pertanian, 2025)
Cabbage production in East Java experienced a decrease in 2019-2021. One of the causes of the decrease in production is the pest Crocidolomia pavonana F. which is the major pest of cabbage (Brassica oleracea) that can reduce production levels up to 79.81%. The study aimed to knowing the response of Crocidolomia pavonana larvae due to application of insecticides from Averrhoa bilimbi extract, Annona muricata extract, and combination of the two and to determine the effectiveness of the combination of insecticides from Averrhoa bilimbi extract with Annona muricata extract. The research was conducted from March to October 2024 at the Agrotechnology Laboratory, University of Jember. The results showed that each plant based insecticides of Averrhoa bilimbi extract, Annona muricata extract, and combination of both had very significant effect on the mortality of Crocidolomia pavonana larvae with treatments P5 (A. bilimbi 20%) and P15 (Combination 20%) able to cause an average mortality of Crocidolomia pavonana larvae 80% with an each LT50 value 114.628 JSA and 120.487 JSA. The Combination Index calculation obtained value of 1.24 which shows that the interaction of combination include in additives so that the combination application is considered less effective in causing mortality of Crocidolomia pavonana larvae than the application of each ingredient.
Reaploud Repository February_Hasyim
Keywords: Crocidolomia pavonana; insecticide; Averrhoa bilimbi and Annona muricata